“Validity” of Vittorio Guidano in the psychotherapy of the twenty-first century - De Pascale, Adele (Revista de Psicoterapia, 2019)
The main purpose of this article is to mention the most important Guidano’s approach contributions to modern psychotherapy and psychopathology. In his cultural and interpretative psychology, rooted in evolutionary epistemology, the mind is the link between the individual and his biology, the external world, and his story. Beginning from the emergence of mentalism among primates, Guidano offers a new explanation of psychosis and psychopathology, for understanding and for curing, based on the integration of three levels of self-meaning: individual, familial, and social. With contextualization, a phylogenic way of remaining connected with the group, as the ontogenic way of child developing that takes place in the family context, through the attachment bonds, it becomes possible to put in sequence the personal experience and integrate it inside the self, to maintain life coherence and continuity. Both psychotherapy and psychiatry are in need of a plausible theory of mind that is able to offer an understanding of basic inherited human feelings, language and meanings as evolutionary tools that are necessary for a functioning health human: the mind and the brain are the same thing. The primacy of affect during the evolution of brain-mind suggests that therapies need a clear vision and knowing of affective human life and what we need is a complete integration of every therapeutic tradition, having the primacy of affective development as the core